Outbreak of Streptococcus pneumoniae serotype 1 pneumonia in a United Kingdom school. (31st December 2008) - Gupta, Atul; Khaw, F-M; Stokle, E L; George, R C; Pebody, R; Stansfield, R E; Sheppard, C L; Slack, M; Gorton, R; Spencer, D A
Abstract : Healthcare workers and teachers should report suspected outbreaks of serotype 1 pneumococcal disease early, and childhood immunisation should be considered